Attachment Styles and Internal Working Models of Children in Takopii No Genzai - Fatimah, Nayla Fadiyah Nusaibatul; Arianingsih, Anisa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study aims to analyze the attachment styles and the Internal Working Models (IWM) of child characters in Takopii no Genzai. This study utilizes a descriptive analytical method. The object of this study is the anime Takopii no Genzai, which is adapted from the manga by Taizan 5. According to John Bowlby’s Attachment Theory, the results indicate that the inability of primary caregivers or parents to instill a sense of security leads to insecure attachment styles and the formation of negative Internal Working Models in three child characters, namely Shizuka, Marina, and Azuma.aw.